2012
DOI: 10.1021/jf2048788
|View full text |Cite
|
Sign up to set email alerts
|

Improved Isolation Procedure for Azaspiracids from Shellfish, Structural Elucidation of Azaspiracid-6, and Stability Studies

Abstract: Azaspiracids are a group of lipophilic polyether toxins produced by the small dinoflagellate Azadinium spinosum. They may accumulate in shellfish and can result in illnesses when consumed by humans. Research into analytical methods, chemistry, metabolism, and toxicology of azaspiracids has been severely constrained by the scarcity of high-purity azaspiracids. Consequently, since their discovery in 1995, considerable efforts have been made to develop methods for the isolation of azaspiracids in sufficient amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(88 citation statements)
references
References 41 publications
2
82
4
Order By: Relevance
“…Recent studies on the toxicity of some purified AZA analogues relative to AZA-1 showed that all analyzed AZAs were toxic and that AZA-2, AZA-3, and AZA-6 were more toxic than AZA-1 by 8.3, 4.5, and 7 times, respectively [10], 37-epi-AZA-1 was 5 times more toxic [11], AZA-33 and AZA-34 were 5 times less toxic and 5 times more toxic, respectively [17], and AZA-36 and AZA-37 were 6 and 3 times less toxic, respectively [15]. As major differences in toxicity can be related to slightly different structures of AZAs, the actual toxicity of the different compounds produced by the Mediterranean A. dexteroporum is worthy of consideration in future toxicological studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies on the toxicity of some purified AZA analogues relative to AZA-1 showed that all analyzed AZAs were toxic and that AZA-2, AZA-3, and AZA-6 were more toxic than AZA-1 by 8.3, 4.5, and 7 times, respectively [10], 37-epi-AZA-1 was 5 times more toxic [11], AZA-33 and AZA-34 were 5 times less toxic and 5 times more toxic, respectively [17], and AZA-36 and AZA-37 were 6 and 3 times less toxic, respectively [15]. As major differences in toxicity can be related to slightly different structures of AZAs, the actual toxicity of the different compounds produced by the Mediterranean A. dexteroporum is worthy of consideration in future toxicological studies.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last years, several analogues of AZA-1 have been discovered either in shellfish [7][8][9][10][11] or in dinoflagellates [6,[12][13][14][15][16][17] and structurally characterized by tandem mass spectrometry (MS/MS) and partly also by nuclear magnetic resonance (NMR) spectroscopy. Some AZAs (AZA-1 and AZA-2, among others) are actually produced by the dinoflagellates, whereas others (e.g., AZA-3 to AZA-19) seem to derive from biotransformation occurring in shellfish [9].…”
Section: Introductionmentioning
confidence: 99%
“…The toxins were purified using a 7 step isolation procedure, the details of which have recently been reported (46). Toxin purity (>95%) was confirmed by LC-MS/MS and NMR spectroscopy and this material was used to 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 using a Fluostar microplate reader (BMG Technologies, NC, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Bruckless, Donegal, Ireland following the 6 th step of a 7 step isolation procedure as described in Kilcoyne et al (2012), and used in trial B.…”
Section: Semi-purified Aza1 Was Obtained From Mussel Tissue (M Edulimentioning
confidence: 99%
“…AZA3 has an AZA1 toxic equivalent factor (TEF) of 1.4 (Ofuji et al, 1999) and concerning the relative in vitro potency of AZA6, it appears to be not unlike that of AZA1 (Dr. M. Twiner, personal communication). are currently available for use as analytical standards, however, nor is there a sustainable way of producing AZA3, an already regulated degradation product of AZA17, other than by complex organic synthesis (Perez et al, 2010) or isolation from contaminated mussels (Kilcoyne et al, 2012;Perez et al, 2010).…”
Section: Introductionmentioning
confidence: 99%